ANALISIS USAHATANI PADI SAWAH DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Ilma Satriana Dewi (DINAMIKA PERTANIAN, 2020)
ABSTRACT Indonesian people still make rice as the main food-producing crop. Rice production shows a significant increase in almost all regions. Thus, many farmers depend on rice farming for their livelihoods, and still run their businesses on a small scale. With a relatively small business scale, causing income derived from rice farming is also relatively lower. The purpose of this study was to analyze the characteristics of farmers and the profile of rice farming, analyze cultivation technology, use of production factors, production, production costs, and rice farming income. Data analysis methods used are descriptive qualitative and quantitative descriptive. The results showed that rice farming was the main occupation of most farmers. The average age of rice farmers is 39.7 years (productive age group). The majority of farmers' education is graduated from junior high school. The average number of dependents is 3-4 families, and farming experience is around 6 to 10 years. Partial land ownership is own land with an average land area of 0,37 Ha. The condition of rice farming is quite good, it's just that there are problems with irrigation that cause farmers to only depend on rainwater. The rice farming revenue is IDR 10.219.500 / growing season which is obtained from the production of 2.271 kg/planting season, with a production cost of IDR 7.037.582 The benefit gained is as much as Rp 3.181.918 / planting season. The efficiency of rice farming is 1,45, which means that rice farming is already profitable. Keywords: Rice, On farm, Production, Revenue.